Use of ambr®250 to assess mucic acid production in fed-batch cultures of a marine Trichoderma sp. D-221704 - Anu Tamminen; Rosaliina Turunen; Dorothee Barth; Virve Vidgren; Marilyn G. Wiebe (AMB Express, 2022)
Key points Trichoderma D-221704 produced 53 g L−1 mucic acid in fed batch culture at pH 4.0 Yeast extract was beneficial, but not essential for good mucic acid production The ambr®250 gave good, reproducible fed-batch cultivations with Trichoderma sp.